Penguasaan Hak Atas Tanah Oleh Pemerintah Daerah Berdasarkan Peraturan Perundang-Undangan Di Indonesia - Primantari, Anak Agung Angga (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
The purpose of writing this article is to carry out an in-depth analysis of the regulation of control over land rights in Indonesia as well as analyzing control over land rights by local governments. The research method used is the normative legal method. The results of the research show that the regulation of land rights in Indonesia is regulated in Article 16 paragraph (1) of Law Number 5 of 1960 concerning Basic Agrarian Principles, the elaboration of which is in Article 20-Article 46 of Law 5/60. Control of land rights owned by the Regional Government in the form of use rights and management rights.